Unamuno´’s God. Vallejo´’s God - Paredes Carbonell, Juan Francisco (Espergesia, 2019)
Unamuno claims that in rationalist thought God is conceived of as a logical, rational, ideal and hypothetical being, away from human nature, because He appears insensitive, unlike the theistic thesis that affirms that God is human, anthropomorphic, personal and authentic, capable of consubstantiating with human nature. In this regard, the Peruvian poet César Vallejo conceives of God, in his poetic discourse, as an indifferent being to man’s problems, far from his suffering and pain; but he also conceives the Supreme Being as the human, biotic, alive and personal God, father of man through Jesus Christ, his son, and there is, therefore, an analogy between Miguel de Unamuno´s divine conception and César Vallejo´s.